Static and Live Digital Forensics, along with practical examples of tools used for each approach - Nurbek Nasrullayev; Homidov Qudratillo Hamza ugli; Tuyboyov Oybek Valijonovich; Djurayev Musurmon Avlakulovich (Zien Journals, 2023)
The field of digital forensics involves examining and analyzing data, with computers being a primary means of communication that investigators can use to gather relevant information. Forensic analysis can be conducted in either a static or live mode. While the traditional static approach may provide incomplete evidence, live analysis tools offer a more precise and consistent view of current and previous processes. Certain critical system-related data stored in volatile memory cannot be effectively retrieved with static analysis techniques. This paper provides a brief overview of both static and live analysis methods and outlines various tools and techniques utilized in digital forensic analysis.
Keywords: Cybersecurity; Digital Forensics; Static Forensic; Live Forensic